The environmental management system based on ISO 14000: Importance of Instrument on the path of environmental sustainability - Martins, Maria Rosa Selvati; Silva, José Geraldo Ferreira da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The environmental issue in recent years, has become a major concern of mankind, both in relation to the extraction of raw materials from the natural environment, and in relation to the effects of models of production and consumption based on the increased demand for products. Faced with this, companies are beginning to recognize the importance of environmental preservation and rational use of natural resources with the same, the legal duty to reassess their operating procedures in order to reduce the negative environmental impacts caused by them. Environmental management emerges as an administrative model aimed at reducing environmental impacts and constant quest for sustainability. The motto, this article aims to look bibliographic knowledge through authors that deal with the subject, addressing and analyzing the importance of the ISO 14000 standard that establishes goals and guidelines and certifies the companies’ commitment to environmental issues.